Peran Pembinaan Terhadap Badan Usaha Milik Daerah Oleh Bagian Perekonomian Sekretariat Tuban - Putri, Arya Pratama Sagita; Prathama, Ananta (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
This research analyses the role of the Tuban Secretariat's Economic, Natural Resources, and Development Administration Section in fostering Regionally-Owned Enterprises (BUMD) in Tuban Regency. The research objective is to identify the role of the Tuban Secretariat's Economic, Natural Resources, and Development Administration Section in fostering Regionally-Owned Enterprises (BUMD) to improve BUMD performance, support Regional Original Revenue (PAD), and local economic development. This research uses descriptive qualitative approach with data obtained through observation, interview, and document analysis. descriptive qualitative with observation, interview, and document analysis methods. The results showed that coaching includes organisation, management, finance, stewardship, asset management, business development, monitoring, evaluation, and administration. Strategies such as routine evaluation, training of managers, preparation of performance contracts, and strengthening governance contribute significantly to the optimisation of BUMD functions. With targeted coaching, BUMDs are expected to be the driving force of the regional economy and improve the quality of public services. This research recommends a sustainable coaching strategy by strengthening collaboration and innovation to achieve more professional management and maximum contribution to regional development.